2015
DOI: 10.1111/1753-6405.12340
|View full text |Cite
|
Sign up to set email alerts
|

The recommended interval for cervical cancer screening: Victorian women's attitudes to an extended interval

Abstract: Aim: To determine Victorian women's knowledge of the recommended Pap test screening interval and support for extending the interval from two years to three years, in light of possible changes to the National Cervical Screening Program.Methods: A random sample of 2,360 women aged 18-69 was interviewed by telephone about their knowledge of the recommended interval, their willingness to change to three-yearly screening if recommended and reasons for their preference.Results: More than 91% of women were aware of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…16 Underscreened women were more accepting of reduced screening frequency (82.5%, P < .05), which may be attributed to the fact that the NCSP now aligns with their existing screening behaviours. 17 Self-sampling acceptability (60.9%) was comparable to a previous study (57.2%). 8 The new program anticipates that self-sampling will overcome some of the barriers to traditional cervical screening.…”
Section: Knowledge and Acceptance Of New Guidelinessupporting
confidence: 79%
See 1 more Smart Citation
“…16 Underscreened women were more accepting of reduced screening frequency (82.5%, P < .05), which may be attributed to the fact that the NCSP now aligns with their existing screening behaviours. 17 Self-sampling acceptability (60.9%) was comparable to a previous study (57.2%). 8 The new program anticipates that self-sampling will overcome some of the barriers to traditional cervical screening.…”
Section: Knowledge and Acceptance Of New Guidelinessupporting
confidence: 79%
“…However, they were still concerned at the potential implications of reduced screening for women's health 16 . Underscreened women were more accepting of reduced screening frequency (82.5%, P < .05), which may be attributed to the fact that the NCSP now aligns with their existing screening behaviours 17 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted in Australia prior to the announcement of the changes have identified women’s concerns about age of first invitation to screen, screening intervals and cost-cutting, so these issues could have been addressed in advance through better communication. 32–34 A potential for cancer to be missed and a suspicion that an increased screening interval was related to cost were major concerns for women described in these publications, and are concerns shared by many commenters in our study. Internationally, publications similarly report that while HPV testing is generally accepted by women, longer screening intervals face opposition.…”
Section: Discussionmentioning
confidence: 66%
“…The interviews followed a topic guide developed using existing literature on previous work about health professionals’ attitudes towards these changes prior to implementation 8,13,16 . The topic guide covered attitudes and expectations pre‐ and post‐implementation of the renewed program, barriers/facilitators to program implementation, clinical practice implications related to the changes, communication of test results, and resources for understanding the changes (Box 1).…”
Section: Methodsmentioning
confidence: 99%
“…Public resistance to changes in the NCSP has been reported, with concerns mainly focused around the extended screening interval 5,6 . Studies conducted prior to the renewal also highlighted health provider recommendation as an important component of women’s acceptance of extended screening intervals 7–9 . Around 80% of cervical screening tests in Australia are performed by general practitioners (GPs) 10 and thus they are likely to play a major role in women’s understanding and experience of the renewed NCSP.…”
Section: Introductionmentioning
confidence: 99%